(untitled) (CIPEEX, 2025)
FinanMaster Aliny de Jesus CostaDavi Gustavo Gonçalves da CunhaFellipe Cotta Pacheco EvangelistaGrazielly Pereira Francisco dos SantoJoão Victor Cabral TockioJulio Cezar Monteiro de SantanaLuiz Eduardo Brazilino de AlbuquerqueMaria Gabrielly Brazilino de Albuquerque The project will be a mobile application for financial education and business management aimed at assisting new entrepreneurs in understanding the concepts behind the financial world and how to build their own businesses, all done in a personalized manner. The application will provide lessons and a learning guide on finance and business, along with tools that allow users to perform operations and simulations to put their acquired knowledge into practice. This will be possible through a teaching approach that brings exclusivity to each student, achieved through an initial questionnaire that classifies the student according to their level of knowledge and risk profile for business management. In this way, a personalized learning path will be created for the student to learn based on their existing knowledge and their preferred learning style, as the educational content will be available in video, text, and mind map formats to accommodate various ways of assimilating information.Moreover, the application will offer calculation and simulation functions for scenarios encountered in business management, which will help them achieve financial goals, such as pricing, projections based on cash flow, and budget creation, without causing any real financial impact. All these resources will generate reports that the student can access to track their progress in lessons and finances, receiving recommendations for future actions.In conclusion, the project aims to enhance accessibility to the financial knowledge necessary for entrepreneurship in a country where many micro-entrepreneurs emerge, who unfortunately, often due to a lack of knowledge, cannot sustain their businesses for more than a year. Thus, quality education will arise for those who have recently started their businesses and for those who do not know where to begin, stimulating the market and potentially reducing social inequality.